2020
DOI: 10.3390/rs13010044
|View full text |Cite
|
Sign up to set email alerts
|

Global Land Surface Temperature Change (2003–2017) and Its Relationship with Climate Drivers: AIRS, MODIS, and ERA5-Land Based Analysis

Abstract: Land surface temperature (LST) plays a critical role in the water cycle and energy balance at global and regional scales. Large-scale LST estimates can be obtained from satellite observations and reanalysis data. In this study, we first investigate the long-term changes of LST during 2003–2017 on a per-pixel basis using three different datasets derived from (i) the Atmospheric Infrared Sounder (AIRS) onboard Aqua satellite, (ii) the Moderate Resolution Imaging Spectroradiometer (MODIS) also aboard Aqua, and (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 81 publications
(76 reference statements)
3
38
0
Order By: Relevance
“…Kozubek et al (2020) indicated that the trend of temperature from ERA5 data has good consistency with observations data. Liu et al (2021) confirmed that the land surface temperature data on ERA5 products are highly consistent with the trend derived from satellite data in 2003-2017. On the regional scale, the research of evaluating the credibility of reanalysis data over China has received extensive attention.…”
Section: Introductionsupporting
confidence: 82%
“…Kozubek et al (2020) indicated that the trend of temperature from ERA5 data has good consistency with observations data. Liu et al (2021) confirmed that the land surface temperature data on ERA5 products are highly consistent with the trend derived from satellite data in 2003-2017. On the regional scale, the research of evaluating the credibility of reanalysis data over China has received extensive attention.…”
Section: Introductionsupporting
confidence: 82%
“…An advantage of ERA5-Land data is the high native horizontal resolution (9 km) while it also offers the capability of long-term hourly or monthly analyses as it covers a time period from 1981 to nearly present (2-3 months before). ERA5-Land provides high-quality information which can be exploited by various climatic studies and interdisciplinary analyses (e.g., [30][31][32]. For this study, we retrieved monthly averaged precipitation, skin temperature (considered as surface temperature), and wind speed data for a 39-year period from January 1981 to November 2020.…”
Section: Climate Datamentioning
confidence: 99%
“…However, the usefulness of such data is poor when the field stations are sparsely distributed 17 . Most model reanalysis datasets, such as the Modern-Era Retrospective Analysis for Research and Applications (MERRA) dataset, National Center for Environmental Prediction (NCEP) products, and the European Center for Medium-Range Weather Forecasts (ECMWF) Reanalysis product ERA-Interim 18 , can provide spatiotemporally continuous LSTs at a global scale. However, these reanalysis datasets are usually output with coarse resolutions, and the effects of surface properties on LSTs are only roughly considered in these numerical models, which are unable to meet the requirements of many applications, which demand LSTs with finer resolution.…”
Section: Background and Summarymentioning
confidence: 99%